Higher Tumor Mutation Burden and Higher PD-L1 Activity Predicts the Efficacy of Immune Checkpoint Inhibitor Treatment in a Patient With Four Lung Cancers. A Case Report - Usuda, Katsuo; Niida, Yo; Iwai, Shun; Funasaki, Aika; Sekimura, Atsushi; Motono, Nozomu; Yamada, Sohsuke; Uramoto, Hidetaka (Frontiers in Oncology, 2020)
We experienced a patient who had four lung cancers with different pathological features, and the most advanced being diagnosed as pStage IIA. A month after the resection the original lung cancer had metastasized to the lung and to the liver. Of the original lung cancers that were resected, the biggest adenocarcinoma of S3 showed 50x31x17mm (invasion 50mm) and pT2bN0M0 (pStageIIA) with epidermal growth factor receptor (EGFR) mutation (-), anaplastic lymphoma kinase (ALK) translocation (-), but expression of PD-L1(+) tumor proportion score (TPS) 80%. The pleomorphic carcinoma showed 23x20x17mm (invasion 23mm) and pT1cN0M0 (pStage Ic) with EGFR(-), ALK (-), PD-L1(+) TPS 95%. Tumor mutation burden (TMB), microsatellite instability (MSI) and structural chromosome aberration analysis by DNA microarray were performed. 100 somatic mutations in the adenocarcinoma and 75 somatic mutations in the pleomorphic carcinoma were identified , which showed an extremely high mutation rate, although, only 16 somatic mutations were common between the two cancers. Chromosomal structural aberrations differed greatly between the two cancers, but common aberrations were found in the chromosome 8 and 10, and partially common aberration in chromosome 4, 14, 17 and X. These results indicated that each lung cancer originated from a common ancestor clone, and developed on an individual molecular evolution. The patient received a single injection of pembrolizumab and 13 injections of atezolizumab. Immune checkpoint inhibitor treatment made metastatic pulmonary and liver lesions reduced in size and showed as PR. Multiple lung cancers with high PD-L1 activity tend to be TMB-high reflecting rapid molecular evolution and relevance to the patient's response to immune checkpoint inhibitors. Genomic examination could help determine what had happened in multiple cancers on progression and provide useful data to patient treatment. Each lung cancer originated from a common ancestor clone, and developed on an individual molecular evolution.